2018
DOI: 10.1016/j.susc.2018.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Complex reactions on a convertible catalyst surface: A study of the S-O-Cu system

Abstract: The interaction of clean and partially oxidized Cu(110) with sulphur was studied by scanning tunneling microscopy and density functional theory calculations in the lowcoverage range. On the clean Cu surface individual S atoms adsorb in the troughs between the Cu atom rows. Hollow sites are preferred, but long-bridge sites are occasionally occupied as well. The majority of adsorbed S, however, seems to be involved in the formation of highly mobile CuxSy clusters of various sizes. The clusters preferentially att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Despite these differences, the common evidence that AgO 2 and AgS 2 complexes can form on the Ag(110) surface is very interesting, and may have broader ramifications, especially for interpreting mass transport. Specifically, it has been observed that both oxygen and sulfur can strongly accelerate coarsening on many coinage metal surfaces 2631 . While M 3 S 3 is a strong candidate on the (111) surfaces, MS 2 and MO 2 are reasonable candidates for (110) and (100) surfaces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these differences, the common evidence that AgO 2 and AgS 2 complexes can form on the Ag(110) surface is very interesting, and may have broader ramifications, especially for interpreting mass transport. Specifically, it has been observed that both oxygen and sulfur can strongly accelerate coarsening on many coinage metal surfaces 2631 . While M 3 S 3 is a strong candidate on the (111) surfaces, MS 2 and MO 2 are reasonable candidates for (110) and (100) surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…A related system, sulfur on Cu(110), has been studied at sub-monolayer sulfur coverages. It was found that S adatoms coexist with possible Cu x S y clusters 31 . No detailed structures of these clusters have been proposed and the clusters were imaged at 77 K, leading to the clusters appearing streaky or fuzzy in STM images due to the clusters being semi-mobile on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…The Cu(0 0 1), Cu (0 1 1), and Cu (1 1 1) slabs include five, seven, and four layer thicknesses [31,32]. In which, we take one bottom corner atom of each slab as the aiming point to put on the adsorption site defined in figure 1 to construct the composite interface.…”
Section: Models and Methodsmentioning
confidence: 99%